2009
DOI: 10.4171/jems/171
|View full text |Cite
|
Sign up to set email alerts
|

Holomorphic functions and subelliptic heat kernels over Lie groups

Abstract: Abstract. A Hermitian form q on the dual space, g * , of the Lie algebra, g, of a Lie group, G, determines a sub-Laplacian, , on G. It will be shown that Hörmander's condition for hypoellipticity of the sub-Laplacian holds if and only if the associated Hermitian form, induced by q on the dual of the universal enveloping algebra, U , is non-degenerate. The subelliptic heat semigroup, e t /4 , is given by convolution by a C ∞ probability density ρ t . When G is complex and u : G → C is a holomorphic function, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…In [6] we have shown that indeed such a unitarity theorem holds if the subLaplacian is merely subelliptic. The inner product on g must, properly speaking, be defined on the dual space g M in this case and is allowed to be degenerate to the extent that Hörmander's theorem for hypoellipticity of the subLaplacian permits.…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…In [6] we have shown that indeed such a unitarity theorem holds if the subLaplacian is merely subelliptic. The inner product on g must, properly speaking, be defined on the dual space g M in this case and is allowed to be degenerate to the extent that Hörmander's theorem for hypoellipticity of the subLaplacian permits.…”
Section: Introductionmentioning
confidence: 95%
“…2. By Hörmander's theorem [16], Lie(H) = g iff is hypoelliptic, see the end of Section 1 in [6] for a more detailed discussion on this last point. So under Hörmander's condition on q, the operator, , in (2·9) admits a smooth heat kernel,…”
Section: Notation and Backgroundmentioning
confidence: 99%
See 3 more Smart Citations